Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Neonatal Fetal Nutrition and Metabolism" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Neonatal Fetal Nutrition and Metabolism" ABS 1. PREVALENCE OF BREASTFEEDING AT 6 MONTHS IN SICK NEONATES • S. Kositamongkol, K. Moungsuwan ABS 2. ROLE OF BREAST MILK AND FECAL MICROBIAL CONTENT IN DEVELOPMENT OF BREAST MILK JAUNDICE • N. Koksal, O. Bagcı, H. Ozkan, I. Varal, P. Dogan ABS 3. VARIABILITY IN THE PROTEIN AND FAT CONTENT OF THE DONOR HUMAN MILK SUPPLY REVEALED BY MID-INFRARED SPECTROMETER ANALYSIS: A FIRST STEP TOWARDS PREVENTING DISRUPTION OF "PERINATAL PROGRAMMING" • V. Rigourd, Z. Assaf, A. Lapillonne, J.F. Magny ABS 4. BOVINE COLOSTRUM FOR PRETERM INFANTS IN THE FIRST DAYS OF LIFE: A RANDOMIZED CONTROLLED PILOT TRIAL • S.M. Juhl, X. Ye, P. Zhou, Y. Li, E.O. Iyore, L. Zhang, P. Jiang, J.B. van Goudoever, G. Greisen, P.T. Sangild ABS 5. PROTEIN AND CALORIC DEFICIT DURING THE NEONATAL PERIOD IN INFANTS WITH BIRTH WEIGHT LESS THAN 1,500 G AND ITS ASSOCIATION WITH BLOOD PRESSURE IN THE ADOLESCENCE • A. Dinerstein, C. Solana, R. Nieto, M. Casale, R. Conti, M. Moiron, F. General ABS 6. EFFECTS OF EXCLUSIVE DONOR HUMAN MILK FEEDING IN A SHORT PERIOD AFTER BIRTH ON MORBIDITY AND GROWTH OF PRETERM INFANTS DURING HOSPITALIZATION • S.H. Chung, E.J. Kim ABS 7. IMPROVED NUTRITION FOR EXTREMELY PRETERM INFANTS - A POPULATION BASED OBSERVATIONAL STUDY • V. Westin, S. Klevebro, M. Domellöf, M. Vanpée, B. Hallberg, E. Stoltz Sjöström ABS 8. POSITIVE RELATIONSHIP BETWEEN TRANSTHYRETIN AND INSULIN-LIKE GROWTH FACTOR 1 DURING THE ANABOLIC PERIOD IN VERY PRETERM INFANTS • I. Hansen Pupp, C. Löfqvist, D. Ley, A. Hellström ABS 9. MEASURING POSTNATAL GROWTH: A COMPARISON OF NEONATAL GROWTH USING INTERNATIONAL INTERGROWTH-21ST STANDARDS AND ESTABLISHED UK CHARTS • O.M. Bendor-Samuel, S. Zivanovic, C.C. Roehr ABS 10. EVALUATION OF MILK AND BLOOD IRISIN LEVELS IN PRETERM NEWBORNS DIAGNOSED WITH EITHER SMALL OR APPROPRIATE WEIGHT FOR GESTATIONAL AGE COMPARED TO FULL TERM NEWBORNS • N. Mól, P. Tomasik, M. Zasada, P. Kwinta ABS 11. ASSAY OF IRISIN CONCENTRATION IN INFANT FORMULAS AND BREAST MILK • N. Mól, P. Tomasik, M. Zasada, P. Kwinta ABS 12. CURRENT PRACTICE AND BELIEFS: SURVEY OF BREAST MILK HANDLING ROUTINES IN GERMAN, SWISS AND AUSTRIAN NEONATAL UNITS REVEALS LARGE CENTRE SPECIFIC DIFFERENCES • D. Klotz, S. Jansen, H. Schneider, C. Gebauer, H. Fuchs ABS 13. ENTERAL FEEDING STRATEGIES FOR VERY LOW BIRTH WEIGHT INFANTS: A NATIONWIDE SURVEY IN JAPAN • M. Ashina, K. Fujioka, S. Totsu, H. Shoji, T. Miyazawa, K. Wada, K. Iijima, I. Morioka ABS 14. DONOR HUMAN MILK MACRONUTRIENT CONTENT: THE EFFECT OF HOLDER PASTEURIZATION  • P. Piemontese, D. Mallardi, N. Liotto, C. Menis, C. Tabasso, M. Perrone, M.L. Giannì, P. Roggero, F. Mosca ABS 15. NEW PARENTERAL NUTRITION AND ACIDOSIS IN PRETERM INFANTS • F. Bonsante, J.B. Gouyon, S. Iacobelli ABS 16. IMPACT ON BREASTFEEDING RATES OF PRETERM INFANTS WITH LESS THAN 29 WEEKS WITH RESTRICTION OF RAW HUMAN MILK IN THE FIRST EIGHT WEEKS OF LIFE DUE TO THE RISK OF PERINATAL CYTOMEGALOVIRUS INFECTION • F.P. Martins-Celini, W.A. Gonçalves-Ferri, B.B. Lima, D.C. Aragon, M.M. Mussi ABS 17. EFFECT OF A NATIONWIDE PROGRAM FOR PROMOTING BREASTFEEDING IN-HOSPITAL IN CHINA • Y. Zhang, H.S. Wang, X. Jin, B. Cao, D.H. Wang, M. Jiang, L.X. Wang, S.M. Wang, W.W. Feng, L.M. Yao ABS 18. VITAMIN D STATUS AMONG PRETERM INFANTS AS A HIGH RISK MORBIDITY MARKER • I. Tofe, M.D. Cañete, M.J. de la Torre, J.L. Perez-Navero, J. Caballero-Villarraso ABS 19. INDIVIDUALIZED GROWTH TRAJECTORIES FOR PRETERM INFANTS USING A GROWTH TRAJECTORY CALCULATOR TOOL • E. Landau-Crangle, N. Rochow, T.R. Fenton, K. Liu, H.Y. So, G. Fusch, A. Ali, M.L. Marrin, C. Fusch ABS 20. PROACTIVE USE OF BREAST MILK FORTIFIER AND BREAST MILK AT DISCHARGE: IS THERE A LINK? A NATIONAL SURVEY OF PRACTICE • S. Stiles, L. de Rooy ABS 21. INFLUENCE OF HUMAN MILK AND PARENTERAL LIPID SOLUTIONS ON SERUM FATTY ACID PROFILES IN EXTREMELY PRETERM INFANTS • A.K. Nilsson, C. Löfqvist, S. Najm, G. Hellgren, E. Engström, P. Lundgren, A.-L. Hård, A. Lapillonne, K. Sävman, M.X. Andersson, L.E.H. Smith, A. Hellström ABS 22. GROWTH AND BODY COMPOSITION UP TO 4 MONTHS OF AGE IN PRETERM INFANTS AND TERM CONTROLS (PEAPOD STUDY) • A. Chmielewska, A. Farooqi, M. Domellöf, I. Ohlund ABS 23. SODIUM SUPPLY BUT NOT HYPERNATREMIA IS ASSOCIATED WITH SEVERE INTRAVENTRICULAR HEMORRHAGE IN EXTREMELY PRETERM INFANTS • C. Späth, E. Stoltz Sjöström, J. Ågren, F. Ahlsson, M. Domellöf ABS 24. COMPARISON OF THE POSTNATAL CATCH UP GROWTH ACCORDING TO THE DEFINITION OF SMALL FOR GESTATIONAL AGE INFANTS • J. Huh, J.Y. Kwon, E.H. Lee, H.R. Kim, K.H. Lee ABS 25. RELATION OF CORD SERUM LEVELS OF INSULIN-LIKE GROWTH FACTOR-I, INSULIN-LIKE GROWTH FACTOR-BINDING PROTEIN-3, GLUCAGON AND LEPTIN ON BIRTH INDICES BETWEEN KOREAN PRETERM AND TERM INFANTS • J.H. Park, S.J. Kang, L.H. Lee, S.Y. Shin, C.S. Kim, S.L. Lee, J.G. Bae, S. Kim ABS 26. USE OF DONOR BREAST MILK IN A TERTIARY NEONATAL UNIT - COMPLIANCE WITH A GUIDELINE • C. Apsey, K, Williams, K. Johnson, H. Shore ABS 27. COPPER AND ZINC CONTENT OF BREAST MILK FROM WOMEN SUFFERING FROM WILSON'S DISEASE • T. Reicherzer, G. Schütze, M. Vogeser, A. Schulze, A.W. Flemmer ABS 28. EARLY ENERGY AND PROTEIN INTAKE AFFECTS GROWTH AND MORBIDITY IN EXTREMELY PRETERM INFANTS • S. Klevebro, V. Westin, E. Stoltz Sjöström, M. Norman, M. Domellöf, A.-K Edstedt Bonamy, B. Hallberg ABS 29. USE OF PROBIOTICS IN PRETERM NEWBORNS. DOES FEEDING TOLERANCE IMPROVE? • M.I. Huescar, M.G. Espinosa, T. Sanchez, E. Salguero ABS 30. VALID AND RELIABLE EARLY IDENTIFICATION OF NEONATAL DYSPHAGIA • M. Viviers, A. Kritzinger ABS 31. EFFECT OF INFANT FORMULA WITH PROTEIN CONTENT OF 1.6 G/100 KCAL FED BETWEEN 3-12 MONTHS ON BODY COMPOSITION AND ADIPOSITY AT AGE 5 YEARS • E.E. Ziegler, D.A. Fields, S.D. Chernausek, D. Grathwohl, J.M. Jeter, S.E. Nelson, M. Chen, N.P. Hays, F. Haschke ABS 32. EARLY-LIFE PROTEIN INTAKE IN INFANTS BORN EXTREMELY PRETERM IS ASSOCIATED WITH HIGHER BLOOD PRESSURE AT SCHOOL-AGE • I. Zamir, E. Stoltz Sjöström, A.K. Edstedt Bonamy, L.A. Mohlkert, M. Norman, M. Domellöf ABS 33. EXTRAUTERINE GROWTH RESTRICTION ASSOCIATED FACTORS IN SMALL AND APPROPRIATE FOR GESTATIONAL AGE INFANTS: A COHORT STUDY • C. Morcelli-Tovar, A.A. Vieira ABS 34. IS THERE ANY ASSOCIATION BETWEEN LAMELLAR BODY COUNTS AND CORD BLOOD VITAMIN D LEVELS OF TERM AND LATE PRETERM INFANTS? • N. Okur, H.G. Kanmaz, M. Buyuktiryaki, H. Bezirganoglu, G.K. Simsek, F.E. Canpolat, N. Uras, S.S. Oguz ABS 35. NEONATAL BODY COMPOSITION OF INFANTS BORN TO MOTHERS WITH GESTATIONAL DIABETES MELLITUS • A.M. Pavel, M. O'Riordan, L. Culliney, T. Nabialek, J. De Meulemeester, F. Caulfield, A. Stanescu, Z. Coffrey, D. Coffey, A. Doolan ABS 36. EFFECT OF ENTERAL IRON SUPPLEMENTATION ON HEALTH OUTCOMES IN PRETERM AND LOW BIRTH WEIGHT INFANTS: A SYSTEMATIC REVIEW • E. McCarthy, M. Kiely ABS 37. NEONATAL INTESTINAL FAILURE IN THE UK - WHO CARES? • R. Jones, P. Cairns ABS 38. PREVALENCE OF PREDIABETES AND TYPE 2 DIABETES IN YOUNG ADULTS BORN WITH VERY LOW BIRTH WEIGHT • M. Talman, P. Nixon, E. Jensen, L. Washburn ABS 39. THE MATERNAL-FETAL GRADIENT OF FREE AND ESTERIFIED PHYTOSTEROLS AT THE TIME OF DELIVERY IN HUMANS • A. Correani, S. Visentin, E. Cosmi, E. Ponchia, S. D'Aronco, M. Simonato, L. Vedovelli, P. Cogo, V. P. Carnielli ABS 40. TRANSIENT POSTNATAL OVERFEEDING IN MICE LEADS TO METABOLIC AND HEPATIC DISORDERS AT ADULTHOOD • C. Yzydorczyk, N. Li, D. Mosig, M. Bidho, B. Keshavjee, J.B.